Evaluation of protection benefit of sand barrier fence with different heights on desert highway - Ming Zhang; Qi Li; Jiayin Hou; Shuai Ji (PLoS ONE, 2025)
As the first barrier of desert highway protection, sand-blocking fence is very important to the safety of the line. Based on the background of Wuma Expressway, this paper uses CFD numerical simulation to study the wind and sand-blocking effect of sand-blocking fence with different heights. The results show that: (1) Between the first and second sand-blocking fences, when the height of sand-blocking fence is 2m, 2.5m, 3.0m and 3.5m, the wind speed near the surface (0.1m ~ 0.3m) is reduced by 87% ~ 97% of the initial wind speed. Between the second and third sand-blocking fences, when the height of sand-blocking fence is 2.5m, the increase of wind speed is 13.87% lower than that of 2m height. The decrease is the largest, and sand particles are easy to deposit here in large quantities. When the height is 2.5m and above, the windbreak efficiency is greater than 90%, and the windbreak effect is significantly improved. (2) The change of sand barrier height has a significant effect on the windbreak efficiency between the second and third sand barriers. (3) Among the three sand-blocking fences, when the height of the sand-blocking fence is 2.5m, the thickness of the sand is 50.51% and 58.33% higher than that of the 2m high sand-blocking fence, and the sand-blocking effect is the most significant. After the height is increased to 3.5m, the thickness of the sand is no longer increased. (4) The height of sand-blocking fence is 2.5m, and the area of sand at the top of embankment is obviously reduced. The area of sand volume fraction 0.55–0.6 is 73.44% lower than that of 2m sand-blocking fence, and the effect of wind and sand prevention is the best.